Performance Monitoring In State-Owned Enterprises: The Case Of Ghana - Tsamenyi, Mathew (The International Journal of Accounting and Business Society, 1999)
A major difï¬culty facing governments around the world is how to monitor the performance of State-Owned Enterprises (SOEs) (Aharoni 1981). This paper reports on research that examines the performance monitoring process in Ghanaian State-Owned Enterprises (SOEs). The analysis presented is based on a case study in three large-scale SOEs. Data is gathered from multiple sources including discussions with accounting ofï¬cials. a review of documents, and interviews with relevant managers in the three SOEs. The results suggest that, the persistent poor performance ot the SOEs resulted in performance monitoring delegated to an external agency established by the government. In theory, the external agency is to monitor all aspects of operations and performance of the SOEs. ln practice. however. major investment and corporate decisions are made by the sector ministry, the ministry of ï¬nance and the respective Board of Directors of each SOE with the external agency having minimal inï¬‚uence in such decisions. KEY WORDS: Management Controls, Budgetary Controls, State- Owned Enterprises, Developing Country, Ghana.